2018
DOI: 10.31083/jin-170035
|View full text |Cite
|
Sign up to set email alerts
|

The role of rosemary extract (40% carnosic acid) in degeneration of hippocampal neurons induced by kainic acid in the rat:The behavioral and histochemical approach

Abstract: Systemic kainic acid administration has been used to induce experimental temporal lobe epilepsy in rats. The aim was to evaluate the neuroprotective effect of rosemary extract (40% Carnosic acid) against kainic acid-induced neurotoxicity in hippocampus and impaired learning and memory. Subjects received a single dose of kainic acid (9.5 mg/kg) intraperitoneally, were observed for two hours, and scored from 0 (for normal, no convulsion) to five (for continuous generalized limbic seizures). Rosemary extract (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In a similar study, GGRE improved memory functions in a mice model of LPS-induced neuroinflammation [ 41 ]. Moreover, RE has been shown to rescue learning and spatial memory deficits in a rat model of epilepsy induced by treatment with kainic acid [ 42 ]. Interestingly, a randomized clinical trial observed that RE treatment positively affected memory performance, anxiety, depression, and sleep quality in 34 Iranian university students [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, GGRE improved memory functions in a mice model of LPS-induced neuroinflammation [ 41 ]. Moreover, RE has been shown to rescue learning and spatial memory deficits in a rat model of epilepsy induced by treatment with kainic acid [ 42 ]. Interestingly, a randomized clinical trial observed that RE treatment positively affected memory performance, anxiety, depression, and sleep quality in 34 Iranian university students [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). GGRE and RE treatments were based on previous studies where similar doses were applied [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The administration of RE and FLX in the present work resulted in a significant decrease in the escape latency and the number of errors indicating an improvement in cognition defects induced by MSG. These RE effects may be due to the induction of neurogenesis in the hippocampus through its antioxidant properties [ 13 , 27 ]. Chronic FLX administration had a significant recovery of the cognitive functions in rats with DG lesions [ 28 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Rosmarinus officinalis (RO) is one of the popular herbs. Its extract has antioxidant properties attributed to its Carnosic Acid, phenolic diterpenes, and Carnosol content [ 13 ]. It has antiviral, anti-inflammatory, cytoprotective, antithrombotic, antidiabetic, and neuroprotective effects partly due to decreasing neuronal oxidative damage.…”
Section: ⧉ Introductionmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining. The pulmonary tissues were dissected from the mice in different groups as described (Naderali et al, 2018). Briefly, the pulmonary tissues were fixed by dipping in 4% paraformaldehyde for 48 hours, then the tissues were embedded in paraffin and cut into 3-4 μm thick slices.…”
Section: Methodsmentioning
confidence: 99%